Answer:6 9/10
Step-by-step explanation:
Answer:
w= -9 :)
Step-by-step explanation:
<h3>
Answer:</h3>
A. 3x² +6
<h3>
Explanation:</h3>
(f-g)(x) = f(x) -g(x) = (4x²+1) -(x²-5) . . . . . substitute the function definitions
... = 4x² +1 -x² +5 . . . . . . . . . . . eliminate parentheses
... = (4-1)x² +(1+5) . . . . . . . . . . . collect like terms
... = 3x² +6
Answer:
k = 7
Step-by-step explanation:
Step 1: Write equation
-18 = 5 - (6k - 19)
Step 2: Solve for <em>k</em>
<u>Distribute negative:</u> -18 = 5 - 6k + 19
<u>Combine like terms:</u> -18 = -6k + 24
<u>Subtract 24 on both sides:</u> -42 = -6k
<u>Divide both sides by -6:</u> k = 7
Step 3: Check
<em>Plug in k to verify it's a solution.</em>
-18 = 5 - (6(7) - 19)
-18 = 5 - (42 - 19)
-18 = 5 - 23
-18 = -18
The Answer is A (The first graph in the photo), I attached the graph to help you see the answer for y-3=-
(x+6).
I hope you have a good day and please give me brainest if that is correct!